Kekuasaan Semantik dalam Analisis Wacana Kritis Debat Capres-Cawapres - Wati Kurniawati; Ririen Ekoyanantiasih; Santy Yulianti; Menuk Hardaniawati; S. S.T. Wisnu Sasangka; Winci Firdaus (Ranah: Jurnal Kajian Bahasa, 2022)
The use of language in relation to the ideology brought by the party in its political speech is important to study in relation to the life of the nation and state. The formulation of the problem in this research is how to use the language of politicians based on semantic power. The purpose of this study is to identify the language of politicians in terms of semantic power. This research uses descriptive and qualitative research methods. The data is taken from transcripts of Jokowi-Amin and Probowo-Sandiaga political speeches. The results showed that speech texts produced by political party figures had utilized linguistic features, such as text structure, vocabulary, language style or figure of speech, sentences, cohesion, coherence, transitivity, and pronouns. Textually, discourse and social show semantic features that are used to launch a social process: the formation of a positive image of a party in fighting for the interests of the people. The social processes and practices channeled by the political party figures are closely related to their social background, politics, and cultural values in particular and Indonesia in general. Verbal discourse in Jokowi-Amin, Prabowo-Sandiaga speeches was expressed in the form of a series of transitive active sentences and intransitive active sentences. Sentences that are expressed are sentences in the form of invitation sentences, exclamatory sentences, sentences of hope, sentences of promises, and sentences of statements. The speech discourses expressed by the orators also contain the use of language styles, namely hyperbole, metaphor, personification, and repetition. AbstrakPenggunaan bahasa yang berkaitan dengan ideologi yang dibawa oleh partai dalam pidato politiknya sangat penting untuk dikaji, terutama dalam kaitannya dengan kehidupan berbangsa dan bernegara. Rumusan masalah dalam penelitian ini ialah bagaimana penggunaan bahasa para politikus berdasarkan kekuasaan semantik. Tujuan penelitian ini ialah mengidentifikasi bahasa para politikus yang ditinjau dari kekuasaan semantik. Penelitian ini menggunakan metode penelitian deskriptif dan kualitatif. Data diambil dari transkrip pidato politik Jokowi-Amin dan Probowo-Sandiaga. Hasil penelitian menunjukkan bahwa teks pidato yang diproduksi oleh tokoh-tokoh partai politik telah memanfaatkan fitur-fitur linguistik, seperti struktur teks, kosakata, gaya bahasa atau majas, kalimat, kohesi, koherensi, ketransitifan, dan kata ganti. Secara tekstual, wacana dalam pidato politik tersebut menunjukkan fitur-fitur semantik yang digunakan untuk melancarkan suatu proses sosial: pembentukan citra positif suatu partai dalam memperjuangkan kepentingan rakyat. Proses dan praktis sosial yang disalurkan oleh tokoh-tokoh partai politik tersebut berkaitan erat dengan latar belakang sosial, politik, dan budaya mereka. Wacana verbal dalam pidato Jokowi--Amin, Prabowo--Sandiaga diekspresikan dalam bentuk rangkaian kalimat aktif transitif dan kalimat aktif intransitif. Kalimat-kalimat yang diungkapan adalah kalimat yang berbentuk kalimat ajakan, kalimat seruan, kalimat harapan, kalimat janji, dan kalimat pernyataan. Wacana pidato yang diungkapkan oleh para orator tersebut juga mengandung pemakaian gaya bahasa, yaitu gaya bahasa hiperbola, metafora, personifikasi, dan repetisi.